Social capital during the coronavirus pandemic: the value of corporate benevolence. Issue 13 (16th March 2022) - Filbeck, Greg; Robbins, Eric; Zhao, Xin
ABSTRACT: In this paper, we explore market reaction to announcements of corporate donations associated with the COVID-19 crisis. Companies with larger firm size, higher leverage, higher institutional ownership, and higher ESG rankings are more likely to donate COVID relief. We observe statistically significant positive abnormal returns over the event window, driven by a subsample of community relief funds. Our results support the notion of a strategic, reputational premium for participating firms. Consistent with signalling theory, we find firms without ESG scores show positive share price responses to corporate benevolence announcements. This finding suggests the market is less likely to anticipate corporate acts of benevolence from firms with missing ESG scores. Our findings suggest that the market positively reacts to corporate philanthropy news during a crisis. The strongest stock market reaction is related to those firms with missing or less favourable ESG scores.